Extremely temperature-resistant, polarimetric radar barcode - Pöpperl, Maximilian; Adametz, Julian; Vossiek, Martin (European Microwave Week 2017: "A Prime Year for a Prime Event", EuMW 2017 - Conference Proceedings; 47th European Microwave Conference, EuMC 2017, 2017)
Chipless radio frequency identification provides a huge potential for applications with extreme environmental conditions. The low data capacities and the printability on film or paper, prevent the use of state-of-the-art realizations in scenarios with extreme temperature. Hence, we introduce a novel chipless RFID tag that overcomes these problems. Due to a polarimetric and image base data encoding, we achieve high data capacities of more than 20 bits. Furthermore we reach an outstanding temperature robustness by avoiding conductive elements and metals. The tag is composed of clay that provides an outstanding temperature resistance and enables low production costs. The tag is suited for applications with temperatures of above 1000°C and consequently opens up new fields of applications for RFID. To show the huge potential of our tag, we describe its operating principle first. Afterwards we perform tests with different tag temperatures in a laboratory.
CRIS-Team Scopus Importer:2023-03-08
Keywords: RFID